Dissecting Growth Pattern : A Variant-Level Examination of the Cryptocurrency Ecosystem - Chauhan, Rashi; Saxena, Shivangi (Indian Journal of Finance, 2026)
Purpose : This study examined year-over-year (YoY) structural growth dynamics across four major cryptocurrency classes—Bitcoin (BTC), Ethereum (ETH), stablecoins, and altcoins, for the period of 2020–2024. Research Methodology : A quantitative approach was employed to analyze YoY market capitalization trends across BTC, ETH, stablecoins, and altcoins, from 2020 to 2024, by using data from CoinMarketCap, by analyzing growth patterns through percentage and absolute market capitalization changes, supported by trend visualizations. A multiple linear regression model assessed the effect of time and asset type, with BTC as the reference category. The analyses were conducted using SPSS version 27. Findings : The findings revealed that 2023 was the period in which none of the cryptocurrency variants performed well due to factors such as regulatory pressure and a global economic slowdown. In contrast, 2024 marked a period of market correction, during which BTC and altcoins experienced a strong resurgence, followed by stablecoins. ETH remained robust throughout the period, supported by decentralized finance (DeFi) applications. Practical Implications : The results indicated that the cryptocurrency market functioned as a network of fragmented yet interconnected components, and continued to develop under a highly volatile and competitive environment. These findings provided important implications for investors, regulators, and scholars interested in the cryptocurrency market structure, risk behavior, and long-run predictability of cryptocurrencies. Originality/Value : This study presented a new application for a venue-specific market cap analysis in cryptocurrency spanning over five years. By leveraging YoY analysis, it provided insights into growth variances, market recovery, resilience, and increasing maturity of the crypto market in response to evolving rules and regulations.